First published record of rodent predation by guira cuckoo in Brazil: notes about vertebrate predation - Oliveira, Seixas Rezende; Hannibal, Wellington; Miranda, Jefferson Eduardo Silveira; de Oliveira, Gustavo Valtuille (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
Guira cuckoo (Guira guira) is a communal breeder bird species displaying a diversified diet. In this study, we report the first published predation event of a rodent by Guira cuckoo in Brazil. We searched for vertebrate predation by this bird species in Brazilian domains in the following databases: Google Scholar, SciELO, Scopus and Web of Science. We recorded the rodent predation event in a landscape composed of pasture and gallery forest in Campo Grande municipality, Mato Grosso do Sul, central-west Brazil. The predated rodent is a vesper mouse, Calomys sp. We found 19 vertebrate species predated by the Guira cuckoo, distributed in all Brazilian domains, within the orders: Anura (5 species), Passeriformes (1), Squamata (12), and Rodentia (1 - present study). Our result contributes to the natural history of the Guira cuckoo, and highlights that this cuckoo bird displays a generalist diet, feeding on a diversity of vertebrate species.